Найти в себе себя: стихи / Александр Мокрушин - Мокрушин Александр Леонидович (Удмуртия, 2019)
Экземпляры: Ф19 (20230310) / Инвентарный номер: 64335 / Цена: 50.00 / Сис.шифр: Р2 / Авт.знак: М 74 / ГРНТИ: 17.82.10 / ББК: 84(2Рос=Рус)6